Peran Pemerintah Kota Dalam Menanggulangi Stunting Di Kota Bontang (Studi Kasus Kelurahan Loktuan Kecamatan Bontang Utara) - Afifah Nur Zahrah; wahid Abdulrahman (Journal of Politic and Government Studies, 2026)
Stunting reduction is a national priority agenda based on Presidential Regulation Number 72 of 2021, which demands a responsive commitment from regional governments. Bontang City, as an industrial center with a large fiscal capacity, still faces fluctuations in stunting prevalence, with Loktuan Village consistently recording the highest accumulation of stunted toddler cases, namely 213 toddlers in June 2025. This study aims to analyze in depth the roles of the Bontang City Government and Loktuan Village in overcoming stunting through the dimensions of regulator, dynamizer, and facilitator functions, as well as to identify the supporting and inhibiting factors of its implementation in the field. Using a descriptive qualitative method, data were collected through in-depth interviews with key stakeholders (Health Office, DP3AKB, Village Government, Community Health Center, and Posyandu Cadres) and analyzed using the data reduction, data display, and conclusion drawing (verification) stages of the Miles and Huberman model. The results show that the government's role as a regulator runs optimally through the strengthening of local regulations, while the role as a dynamizer is the most effective dimension through the mobilization of Corporate Social Responsibility (CSR) funds from surrounding industrial companies to overcome local budget constraints. However, the role as a facilitator still faces obstacles in the form of bureaucracy, a lack of permanent posyandu buildings, and supplementary feeding programs that are temporary in nature. Despite these constraints, this collaborative intervention successfully reduced the stunting prevalence rate in Loktuan Village progressively from 24.14% to 15.74%.